Notary's Responsibility In Making A Deed Under Hand With A Signature On A Blank Stamp By The Face - Nurdiana Arini, Etnavita (International Significance of Notary, 2023)
Abstract : A notary as a public official has the authority to make a deed in accordance with the Notary Office Law and the notary code of ethics. Making an authentic and underhand deed can be burdened with responsibility for his actions in connection with his work in making the deed. There is deviant behavior by notaries who abuse the making of deeds signed by the face on blank stamps. The research method used in this study is to use normative juridical research methods, using a statute approach and a comparative approach. The result of the discussion of this study is that the legal relationship that occurs on an empty stamp is a civil relationship and the legal basis is contained in article 1338 of the Civil Code. The legal conditions of the agreement are regulated in article 1320 of the Civil Code which consists of four conditions and each is qualified in two elements. Signing a deed under hand using a blank stamp will have legal consequences that are null and void. null and void due to non-fulfillment of elements of the legal conditions in the agreement which if it violates objective conditions i.e. agreements made with prohibited causa or false causa committed by a notary. because the filling of the deed includes unlawful acts that have been regulated in article 1365 of the Civil Code.The notary's responsibility for misuse of blank blanks in making deeds under hands that are not in accordance with the notary law can be held responsible both in terms of administration in the form of sanctions and has been regulated in the Notary Office Law, namely oral reprimand, written reprimand,  Temporary suspension, dismissal with respect to dishonorable dismissal.Keywords: Notary, Deed Under Hand, Blank Sign, Unlawful Deeds